Biosaline Agriculture and Salt Tolerance of Plants - Gheyi, Hans; de Lacerda, Claudivan Feitosa; Sandhu, Devinder (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The salinity of soil and water is a problem present in all continents, especially in arid and semi-arid regions. Worldwide data indicate that 20% of the total cultivated area (upland and irrigated) and 33% of irrigated agricultural land are affected by excess salts in the soil. Furthermore, a significant number of the water sources in these regions, notably groundwater, have high concentrations of salts, which is a limiting factor for agricultural production. On the other hand, the growing demand for food because of population increases, the scarcity of water resources and land for the expansion of agriculture, and global climate change scenarios indicate the need to use these saline resources. In this context, biosaline and HALO agriculture appear to be some of the sustainable tools to increase food production and create job opportunities and sources of income for farmers. In this Special Issue, successful examples of biosaline agriculture in different parts of the world are presented, as well as studies on crop tolerance to salinity, strategies to mitigate salt stress, and the bio-remediation of salt-affected soils. Therefore, this Special Issue brings relevant contributions to sustainable agriculture using saline resources, and the published knowledge can be useful for students, professionals, and farmers.